Intrapleural injection of urokinase in the treatment of acute Haemophilus influenza empyema in children: A case report and literature review - Yang, Lin; Zhu, YaFei; Wu, GuangSheng (Frontiers in Pediatrics, 2022)
【Abstract】Objective:The purpose of this study is to analyze the clinical data of a child with acute empyema caused by Haemophilus influenzae, and to investigatethe diagnosis and treatment of thisdisease through literature review, in orderto improve the clinical understanding of this kind of disease. Methods: A 6-year-old female with acute H. influenzae empyema was treated at the Department of Pediatrics of The Affiliated Hospital of Hangzhou Normal University, Hangzhou, China. The pleural puncture fluid turned out to be yellow turbid pus, and the pleural effusion was diagnosed as empyema according to theclassification of pleural effusions. High-throughput sequencing revealed the presence of H. influenzae. After comprehensive treatment,includingantibiotic, closed pleural drainage and intrapleural injection of urokinase, the pleural effusion was absorbed and discharged. A systematic literature search inPubmed, Embase, Scopus, CNKI, Wanfang and VIP Chinese databases revealed no cases of acute empyema in children caused by H. influenza and treated with urokinase . Results There were no bronchopleural fistula and tension pneumothorax during the treatment. One month after discharge, chest computed tomography (CT) revealed no pleural thickening and normal pulmonary function. Conclusion Pneumonia inthe child worsened after an initialimprovement of symptoms, which is an issue that requires further medical attention. High-throughput sequencing of pathogens in pleural effusion can improve the detection rate. This study indicated that closed pleural drainage combined with intrapleural injection of urokinase is an effective treatment for H. influenzae empyema in children.